KESALAHAN KALIMAT DALAM TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 12 PADANG - Riduan, Riduan; R.,, Syahrul; Manaf, Ngusman Abdul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTThe background of this research is the students’ ability of writing the report of observation’s result text is low, which one of the factors that cause it,  is sentence error. The purpose of this research is to describe the sentence error in the report of observation’s result text which is reviewed by these aspects (1) the structure of syntax’s function, (2) the deficiency of sentence’s element (3) the excrescent of the sentence’s element, (4) the error of reasoning arrangement. This type of the research is qualitative with the descriptive method. The instrument of the research is the reseracher himself. The data of this reseach is the error sentences.  The source of the data’s research is achieved from the report of observation’s result text of the VII 1 grade in SMP Negeri 12 Padang. The data is analyzed through these steps (1) Identifying the general description and data’s coding, (2) Data Inventory, (3) Identifying the forms of the sentence error, (4) Analyzing the sentence error and, (5) Concluding the result of the research. The results of this research as follows. First,the sentence error on the aspect of syntax structure is the error of the use of the predicate. Second, the sentence error on the deficiency of sentence’s element is there is no subject, lack of independepnt clause, lack of conjunction,  and there is no affix in the root that should be added by affix. Third, the sentence error on the excrescent of the sentence’s element is the overlap of the use of plural indicator, redundancy, and the inappropriate affix on the root. Fourth, The sentence error on reasoning arrangement is the meaning  of the sentence is not logical, and the error of the choice of words to explain the meaning of the sentence Key words : Sentence error, the report of observation’s result text.Kata Kunci: Kesalahan Kalimat, Teks Laporan Hasil Observasi